ZOONYMIC IMAGERY IN PROVERBS: A LINGUOCOGNITIVE AND LINGUOPRAGMATIC STUDY OF ENGLISH AND UZBEK PAREMIOLOGY (Educator Insights: Journal of Teaching Theory and Practice, 2026)
Paremiological units represent an important layer of linguistic heritage reflecting collective experience and cultural knowledge of a society. Among the expressive means widely used in proverbs are zoonymic components, which include the names of animals functioning as metaphorical representations of human qualities and social relations. The present study focuses on the linguocognitive and linguopragmatic analysis of proverbs containing animal imagery in English and Uzbek languages. The research aims to identify conceptual associations between animal behavior and human characteristics as reflected in paremiological discourse. The findings indicate that animal-based metaphors play a significant role in shaping linguistic worldview and serve important communicative functions such as evaluation, warning, advice and social commentary.